Gambaran Hematologi dari Pemberian Anestesi Kombinasi Ketamin-Xilazin dan Ketamin-Diazepam pada Pelaksanaan Kastrasi Anjing - Utami, Tri; Tophianong, Tarsisius Considus; Semarabawa, I Gede; Darang, Calvin Lummu (JURNAL KAJIAN VETERINER, 2024)
Carrying out castration on dogs requires anesthesia to prevent movement and relieve pain during the operation. The aim of this study was to determine the effect of administering two combinations of general anesthesia, ketamine - xylazine and ketamine-diazepam on the blood features of dogs undergoing castration procedures. The dogs used in this study were 6 dogs, domestic breed, male and aged between six months and one year. Blood sampling from the cephalic antebrachii vein of 1 ml was carried out twice, thirty minutes before surgery and sixty minutes after surgery. The average results of post-operative complete blood tests in dogs given ketamine (10 mg/kg body weight, iv) – xylazine (1 mg/kg body weight, iv) anesthesia, include: total erythrocyte count 5.84 x 106/µL, haemoglobin 12.27 g/dL, haematocrit 36.7%, and leukocytes 15.4 x 103/µL. The average results of post-operative complete blood tests in dogs given ketamine (10 mg/kg body weight, iv)–diazepam (0.2 mg/kg body wight, iv) anesthesia, include: total erythrocyte count 5.98 x 106/µL, haemoglobin 11.77 g/dL, haematocrit 36.23%, and leukocytes 16.4 x 103/µL. Based on the results of statistical analysis using the independent t-test, the number of erythrocytes, haemoglobin, haematocrit and post-operative leukocytes between the two groups was not significantly different (P>0.05). The use of the combination of ketamine-xylazine and ketamine - diazepam during castration did not cause changes in the number of erythrocytes, haemoglobin, haematocrit and leukocytes.